Sociodemographic factors associated with premarital sex activity among school-going late adolescents in Kuantan, Pahang - Zainuddin, Nur Akmanidar; Abdullah, Fa’iza; Draman, Samsul; A. Rahman, Nor Azlina; Muhammad, Noor Azimah (2019)
Most of the premarital sex among adolescents are unprotected lead to increasing the risk of sexually transmitted infections and increment number of teenage pregnancies (Azri, Suan, Ismail, Medicine, & Ghazali, 2015). According to the National Health Morbidity Survey 2017, Pahang is the highest state of adolescent aged 13 to 17 years old with ever having had sex (9.5%). The purpose of this study is to identify the sociodemographic factors associated with premarital sex among school-going late adolescent in Kuantan, Pahang. A cross-sectional study was conducted among 466 unmarried students aged 18 to19 years old from nine government secondary schools in Kuantan district. Sociodemographic and relevant data were collected using a self-administered validated questionnaire. Statistical analyses were done using IBM SPSS version 22.0. Majority of the participants were females (64.4%), Muslims (68.2%) and Malays (67.4%). Prevalence of premarital sex among school-going late adolescent was 1.5% predominantly by males (85.7%). Simple logistic regression showed being female had a lower risk to have premarital sex compared to male (p=0.026, OR: 0.089 CI: 0.011-0.747) and current smoker had a lower risk to perform premarital sex compared to non-smoker (p=0.003, OR: 0.083 CI: 0.016-0.428). In the multivariate logistic regression, again being female was identified as having a lower risk to perform premarital sex compared to male (p=0.026, OR: 0.066 CI: 0.006-0.721). In conclusion, the risk to perform premarital sex was found to be higher among males than female thus comparable to the greater prevalence of male premarital sex experienced. Therefore, the influence of family interaction and parenting behaviors on premarital adolescent sexual decision needs to be explored further across gender.